Contextual searches of the architectural space and green structure of Bauska Old Town - Ziemeļniece, Aija (Journal of Architecture and Urbanism, 2013)
The cultural heritage is a potential resource for ensuring quality of human life and sustainable development. The urban environment, in which we live, is not frozen, it is constantly developing. Each time it leaves footprints in the space that can enrich or downgrade its architecturally compositional expression. The environment is constantly changing due to human ambitions, errors and actions. For the preservation of cultural space and development, interdisciplinary cooperation and understanding is required. Identity maintenance of the urban space of Bauska is mainly associated with identification, restoration and preservation of cultural and historical sites as well as care and protection of the landscape space specific to this site. Under the impact of the green cover of the river bank it is visually hard to see the place of rapids. This also applies to the balanced green area in the town’s historical centre.